Nutrient reduction from vinasse by Chlorella vulgaris microalgae (Research, Society and Development, 2020)
The sugar-alcohol industries are responsible for the production of ethanol and sugar; however, a byproduct is generated in large quantities in this production, as vinasse that has high pollutant power and high fertilizing value. Much of the vinasse is used for fertigation, however, plants have encountered difficulties due to soil saturation after a period of use. This soil saturation highlights the high concentration of some nutrients, especially potassium, which can impair plant growth due to nutrient imbalance. The objective of this work was to treat the vinasse from a sugarcane plant with the use of Chlorella vulgaris (Kessler & Huss, 1992), microalgae, aiming to reduce some nutrients present, especially potassium, to ensure better reuse of this in the fertigation of sugarcane. The results showed the efficiency of treatment using microalgae in reducing potassium, sodium and calcium concentrations. These reductions make the vinasse more available to be used for fertigation in the company's sugarcane fields, which consequently reduces the purchase of mineral fertilizers, thus closing an ecological cycle of production and reuse of the waste generated.